(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The service process is the key phase in any queue system applied to business and industry operations. The service process in shops is defined as the payment process at the cash register. The service process consists of two elements or sub-processes: the waiting in the queue to the cash register as well as the payment processing (scanning the goods, giving receipts to customers, etc). Analysis of burstiness as the indicator of the service process has been well-established. Against this background on burstiness as the indicator of the service process, burstiness is also defined as a factor that influences the service process. However, burstiness as a factor in the service process has not attracted a lot of research attention. The aim of this paper is to analyse burstiness as a factor in the service process underpinning the elaboration of scenarios of the service process for the queue management purposes. The present work mostly employs theoretical methods: scientific literature analysis, synthesis, modelling, comparison, and systematization. The theoretical research results in the outline of the conceptual framework for exploring the impact of burstiness on the service process. The key concepts have been identified, namely binary customer behaviour, buyers’ burstiness, bottlenecks’ emergence at the server, and queue management. The logical chain of the development has been emphasized: binary customer behaviour → buyers’ burstiness → bottlenecks’ emergence at the check-out station or cash register (server) → queue management. The presented logical chain allows finding out that buyers’ burstiness leads to the queue appearance in the service process. In turn, queue appearance requires queue management measures. Hence, buyers’ burstiness influences on the decisions in regard to queue management within the service process. Further on, two functions of buyers’ burstiness are defined: the indicators of the service process, and the factor that influences the service process. This bi-modal role of buyers’ burstiness in the service process highlights the complex nature of the queue management. Five scenarios of the service process will allow using a combination of queue management measures in each scenario or even between scenarios. The findings of the comparative study propose the structure of the service process as the unity of the waiting in the queue to the cash register and the payment processing at the cash register, i.e. scanning of the goods and the payment. The present research has some limitations. Further research tends to validate the model of five scenarios of the service process for the queue management purposes. Comparative studies on buyers’ burstiness in the service process will be continued, too.